2014
DOI: 10.1007/s10068-014-0216-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the stability of garlic thiosulfinates

Abstract: Despite a potent antimicrobial activity, garlic (Allium sativum L.) has not been used as a commercial food preservative because of instability of the antimicrobial activity, among other reasons. Factors influencing the stability of thiosulfinates in garlic were investigated to improve understanding of the antimicrobial activity of garlic in food preservation. As temperature, pH, the garlic concentration, and the liquid oil content increased, the stability of thiosulfinates decreased. Thiosulfinates were more u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Particularly, GSAk derivatives were seriously affected, showing a mean recovery of 42.7%. This marked a decrease in their concentration is likely due to the great instability of these compounds under alkaline pH conditions (intestinal digestion), consistent with earlier reports [41]. Moreover, compounds, such as methiin, deoxymethiin, S-(2-carboxypropyl) cysteine, GSMC, and γ-Glutamyl-S-(S-1-propenyl) cysteine-glycine, were not detected after the intestinal phase.…”
Section: Bioaccessibility Of Organosulfur Compounds After Simulated Gastrointestinal Digestionsupporting
confidence: 91%
“…Particularly, GSAk derivatives were seriously affected, showing a mean recovery of 42.7%. This marked a decrease in their concentration is likely due to the great instability of these compounds under alkaline pH conditions (intestinal digestion), consistent with earlier reports [41]. Moreover, compounds, such as methiin, deoxymethiin, S-(2-carboxypropyl) cysteine, GSMC, and γ-Glutamyl-S-(S-1-propenyl) cysteine-glycine, were not detected after the intestinal phase.…”
Section: Bioaccessibility Of Organosulfur Compounds After Simulated Gastrointestinal Digestionsupporting
confidence: 91%
“…In the present case, both factors were more pronounced in the sausages from organic pork. Furthermore, for garlic extracts (thiosulfanates), decreasing stability was reported with increasing degree of fatty acid unsaturation [38]. Garlic extracts were also found to be surprisingly unstable when stored in liquid vegetable oil [39], which has high PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be related to their stability as many flavour compounds are known to be highly unstable and prone to oxidative degradation (Turek and Stintzing, 2013). Lee et al (2014), for instance, reported a decreased stability of garlic-derived thiosulphinates in the presence of increased amount of unsaturated fatty acids. This is in line with higher levels of PUFA and oxidation markers (TBARS) observed in the present study for ECO sausages.…”
Section: Discussionmentioning
confidence: 99%